2011
DOI: 10.4314/tjpr.v10i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of <i>Oldenlandia diffusa</i> Suppresses LPS-Induced iNOS, COX-2 and TNF-α Expression in RAW 264.7 Cells via the NF-κB Activity

Abstract: Purpose: To elucidate the anti-inflammatory mechanisms of aqueous extract of Oldenlandia diffusa (AEOD) in cells. LPS-induced mRNA and protein expression of iNOS, COX-2 and TNF-α were attenuated by treatment with AEOD. These data imply that AEOD tightly regulates the expression of these inflammatory mediators at the transcriptional level. Therefore, we determined the effects of AEOD on nuclear factor-κB (NF-κB) activity, which has been considered to be a potential transcriptional factor for regulating the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Among them, TNF-α and IL-6 were considered as the most important inflammatory mediators in innate immune response [11]. Transforming growth factor β (TGF-β) has been shown to play an anti-inflammatory role in immunity and autoimmunity [12].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, TNF-α and IL-6 were considered as the most important inflammatory mediators in innate immune response [11]. Transforming growth factor β (TGF-β) has been shown to play an anti-inflammatory role in immunity and autoimmunity [12].…”
Section: Discussionmentioning
confidence: 99%
“…Oldenlandia diffusa also suppressed the LPS-induced DNA binding activity of NF-κB to induce the production of NO, PGE2, and TNF-α by regulating the activation of NF-κB. 7 Deng et al reported the use of Oldenlandia diffusa in phytotherapy for the management of psoriasis. Phytotherapy (PT) interventions included oral administration of single or multiple PTs or extracts thereof.…”
mentioning
confidence: 99%